Study about Artificial Intelligence: An Approach towards Robots and Philosophy in Surgery - Hinzpeter, Jaime (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
In terms of AI (Artificial Intelligence), so much progress has been made in two years ... The first thing that comes to mind is mathematician Alan Turing who, when philosophizing about a problem that pretended not to attend a part, concluded with: Writing papers that could be the cornerstone of current computer technology [1]. All efforts to equip computer systems with certain capabilities are summarized under the term AI (Artificial Intelligence) [2]. The subject is intriguing and can even terrify you, because of course conflict arises as events and potential dangers loom around the corner. It is not that AI (artificial intelligence) opens a door that is forbidden a priori (if a metaphysical similarity is possible), but rather that it reveals a very fundamental challenge, namely its correct development. The task of infusing an intelligent machine with complicated concepts like justice, kindness, and love is already complicated, but work is already being done on it. What would Turing think of an intelligent machine? High-performance machines are present in medicine today and will continue to be so. Jesús Moreno, doctor of the Spanish Society for Laparoscopic and Robotic Surgery says: "In 10 years, robots will be used more often in the operating room." 4 The updated history of robotic surgery [3] begins with the PUMA 560 (\(^{°}\) r), which has developed into 2 prototypes, PROBOT (\(^{°}\) r) and ROBODOC (\(^{°}\) r) for prostatectomy or trauma surgery. The AESOP, an endoscopic system for abdominal surgery, is primarily a robotic arm that carries a laparoscopic camera. Towards the end of the century, the ZEUS (\(^{°}\) R) robot appeared and expanded its range of application to include the integration of urology. The Zeus robot is a large 3-armed robot; a left and a right arm simulate the surgeon's arms plus a third arm controlled by an AESOP voice control. This is how the DA VINCI (\(^{°}\) r) robotic surgery system was created, consisting of 3 elements: a visualization trolley, the surgeon's console (arms with 7 sliding areas and a computer system with 3D images) and the mobile car (with more arms). This robot was developed by the SRI (Standford Research Institute), the first copy of which came on the market in 1997 [4] and was visibly approved by the FDA. Perhaps its downside is that it is still a large robot with many connections. In the 21st century, we've seen gigantic advances in robotic surgery, both in terms of models and sizes. Also impressive. (I would say downright scary) Or the author Isaac Asimov? Who was still far from the digital age when he published his book I Robot in 1950? Today, the two of them could be witnesses of AI (artificial intelligence) in any of its magnitudes and magnificence, which act as digital assistants not only for mobile phones, but also for social networks such as Facebook, Microsoft or Google [5]. But be careful, Nick Bostrom emphasizes in an interview this year: If we cannot control it, we could give room to the reality of a super-intelligent system that could prioritize the achievement of its own values at the expense of our own [6]. Two years ago, before this interview, the Swedish philosopher had already said about superintelligence.